Boosting Productivity in Russia Skills, Education and Innovation - Demmou, Lilas (OECD Economics Department Working Papers, 2015)
The labour market in Russia is very flexible. Firms adjust to economic shocks through wage cuts, working hour reductions and minimisation of non-wage labour costs. Workers react by changing jobs. This results in a high and stable overall employment rate, but also high wage inequality, informality and labour turnover, which limits incentives for firms to invest in human capital and productivity improvements. While educational attainment is very high, the education system needs to be strengthened to respond to the needs of a skill-based economy. School-employer cooperation is low and opportunities for higher education are unequally distributed. Adequate funding for education institutions is not assured everywhere while inefficiencies persist. Private spending on innovation is very low and Russia underperforms in terms of scientific outputs and patents. Support for low-tech innovation and technology adoption, especially among SMEs is narrow because of a bias towards large and high-tech projects, which however are only loosely related to Russian manufacturing capacity. Reform of the public R&D sector is incomplete, notably with respect to strengthening funding on a competitive basis